A Literature Review On The Development Phases Of Hungarian Pig Industry (1945 - 1989) Part I - Vinkler Belane; Csilla Kalmar-Rimoczi; Beatrix Lenkovics (European Scientific Journal, ESJ, 2016)
Pig farming enjoys a significant tradition in Hungary and the pig industry plays a key role within the domestic animal husbandry sector. Raising pork has always played an important role in the domestic meat supply, but it has a crucial role in supplying the export markets. It can be concluded that our natural resources provide in themselves significant comparative advantages for us with a high proportion of arable land in agricultural use. Our social and economic endowments and potentials are also favourable for agricultural production and stock-raising. Our paper aims to employ financial data to describe the development of raising pig livestock in Hungary best characterized by its constant changes. Part I summarises two periods describing the changes affecting the animal husbandry sector and their subsequent impact on the economy. On the one hand, it covers the period following World War II, from 1945 to 1965, describing the situation of the country and the farmers; on the other hand, it lists the economic achievements and their impact on the pig industry preceding the political-economic transition in the course of the years lasting from 1966 to 1989.